Uso de aparelho de amplificação sonora individual por idosos: estudo SABE - saúde, bem- estar e envelhecimento - Cruz, Mariana Sodário; Lima, Maria Cristina Pereira [UNESP]; Santos, Jair Lício Ferreira; Duarte, Yeda Aparecida De Oliveira; Lebrão, Maria Lucia; Ramos-cerqueira, Ana Teresa De Abreu [UNESP] (Academia Brasileira de Audiologia, 2013)
PURPOSE: Describe hearing aid use by the elderly population in the city of São Paulo and identify associated factors. METHODS: A cross-sectional, descriptive, quantitative study integrated with the SABE (health, well-being and aging) project developed in 2006. A total of 1.115 individuals aged 65 or over were interviewed. Sample selection occurred in two stages, with replacement and probabilities proportional to the population to complement those aged 75 or over. Structured questionnaires and validated instruments were used. The data were weighted, the Rao-Scott test was used for univariate analysis and backward stepwise logistic regression was used for multivariate analysis, performed on Stata 10® software. RESULTS: Three hundred and seventy-seven subjects (30.4%) were classified as hearing impaired and 10.1% of these reported using hearing aids. To acquire the devices, 78.8% used their own resources and 16.9% acquired them through the Brazilian public health system (SUS). Among non-users of hearing aids, 16.6% reported prior indication; however, 8.6% were unable to adapt to the device and 8.0% could not afford to acquire one. Hearing aid use was associated with lower prevalence of probable dementia. CONCLUSION: The low number of hearing aid users indicates the difficulties elderly people face in acquiring them and/or that the health services face in effectively helping them to adapt. These findings may influence the quality of life of elderly with hearing impairment, given the association with probable dementia revealed by this study.

OBJETIVO: Descrever o uso do aparelho de amplificação sonora individual (AASI) pela população idosa do município de São Paulo e fatores associados. MÉTODOS: Estudo transversal, descritivo e quantitativo, integrante do Estudo SABE (Saúde, Bem-estar e Envelhecimento), desenvolvido no ano de 2006. Foram entrevistados 1115 sujeitos com 65 anos ou mais. A amostra foi obtida de setores censitários em dois estágios, com reposição e probabilidade proporcional à população, complementando-se para acima de 75 anos. Utilizou-se questionário estruturado e instrumentos validados. Os dados foram ponderados e a análise foi realizada no software Stata 10®, através do teste de Rao-Scott para análise univariada e regressão logística tipo stepwise backward para análise multivariada. RESULTADOS: Trezentos e setenta e sete sujeitos (30,4%) apresentaram deficiência auditiva autorreferida e destes, 10,1% declararam utilizar o AASI. Dentre as formas de aquisição do dispositivo, 78,8% utilizaram recursos particulares e 16,9% adquiriram via Sistema Único de Saúde (SUS). Dentre os não protetizados, 16,6% relataram indicação prévia. Entretanto, 8,6% não se acostumaram e 8,0% não adquiriram, por problemas financeiros. O uso do AASI associou-se à menor prevalência de provável demência. CONCLUSÃO: O baixo número de usuários de AASI indica dificuldades dos idosos em adquiri-lo e/ou dos serviços de saúde em adaptá-los de forma efetiva. Esse achado pode influenciar a qualidade de vida do idoso deficiente auditivo, visto a associação com a provável demência, revelada pelo presente estudo.
Hearing aids use among elderly: SABE study - health, well-being and aging survey
Keywords: Envelhecimento; Demência; Auxiliares de audição; Perda auditiva; Inquéritos de morbidade; Aging; Dementia; Hearing aids; Hearing loss; Morbidity surveys